Keeping Community Stakeholders Informed About the Rationale for Program Changes - Kirsten Limpert; John Morton (The Advocate, 2017)
Communication is the key element in much of education. Gathering input and utilizing the information to help educators understand community perceptions is a vehicle that has long been underutilized in schools. This article will examine the historical perspectives of involvement and communication and provide concrete suggestions for keeping all stakeholders informed about the continually changing landscape of education. The authors use communication about Common Core State Standards as an example for keeping stakeholders informed about school change.